Information Systems Foundations: Constructing and Criticising - Hart, Dennis; Gregor, Shirley (Information Systems Foundations, 2005)
This volume contains the papers presented at the second biennial Information Systems Foundations ('Constructing and Criticising') Workshop, held at The Australian National University in Canberra from 16-17 July 2004. The focus of the workshop was, as for the first in the series, the foundations of Information Systems as an academic discipline. The particular emphasis was on the adequacy and completeness of theoretical underpinnings and the research methods employed. At the same time the practical nature of the applications and phenomena with which the discipline deals were kept firmly in view. The papers in this volume range from the unashamedly theoretical ('The Struggle Towards an Understanding of Theory in Information Systems') to the much more practically oriented ('A Procedural Model for Ontological Analyses'). The contents of this volume will be of interest and relevance to academics and advanced students as well as thoughtful and reflective practitioners in the Information Systems field.